Respons awal pemberian biostimulan Orgamin pada kelapa sawit (Elaeis guineensis Jacq.) di Kebun Marjandi PTPN IV Early response of Orgamin biostimulan application in oil palm (Elaeis guineensis Jacq.) at PTPN IV Marjandi plantation - Soekarno Mismana PUTRA; Djoko SANTOSO; Happy WIDIASTUTI; A. H. SARAGIH SARAGIH; M. A. GHONI GHONI; B. MARAHIMIN MARAHIMIN; K. PANJAITAN PANJAITAN (E-Journal Menara Perkebunan, 2013)
AbstractEffort to increase the production of oil palm can beconducted through application of plant growth regulator(PGR). Orgamin biostimulan is a natural PGR formulathat has been tested to improve the vegetative growths ofcorn and oil palm in the glass house. Assessment ofOrgamin and Orgamin plus (Orgamin + micro nutrient)applications at commercial scale was carried out inMarjandi oil palm plantation of PTPN IV usingrandomized block design with three treatments, i.e. K =100% recommended dose of inorganic fertilizer(control), O= Orgamin (1.5 kg/tree) + 50% dose ofinorganic fertilizer, OP = Orgamin plus (1.5 kg/tree)without inorganic fertilizer. The parameters ofobservation at 2.5 months after the treatments were soiland leaf nutrient contents (N, P, K, Mg), percentage offemale flower, mesocarp oil content, and harvested freshfruit bunches (FFB). The observation showed that therewas an increased in oil yield, weight of FFB and leafnutrient content, while the percentage of female flowerand nutrient content of soil were not significantlydifferent compared to the control.AbstrakUpaya untuk meningkatkan produksi kelapa sawitdapat dilakukan antara lain melalui pemberian zatpengatur tumbuh (ZPT). Biostimulan Orgamin merupa-kan formula ZPT alami yang telah diuji di rumah kacapada tanaman jagung dan bibit kelapa sawit. Uji cobaaplikasi Orgamin dan Orgamin plus (Orgamin yangdiperkaya hara mikro) pada skala lapang dilakukan dikebun kelapa sawit Marjandi PTPN IV denganmenggunakan Rancangan Acak Kelompok (RAK) untukmenguji tiga perlakuan, yaitu 1) K (kontrol) = 100%dosis anjuran pupuk kimia (APK = kontrol), 2) O = 50%dosis APK + Orgamin (1,5 kg/pohon), 3) OP = Orgaminplus (1,5 kg/pohon) tanpa pupuk kimia. Peubah yangdiamati pada 2,5 bulan setelah perlakuan adalah kan-dungan hara tanah dan daun (N, P, K, Mg), persentasebunga betina, rendemen minyak mesokarp, dan produksitandan buah segar (TBS). Hasil yang diperoleh menunjukkan terdapat peningkatan rendemen minyak, bobotTBS dan kandungan hara daun, sedangkan persentasebunga betina dan kandungan hara tanah tidak menunjuk-kan perbedaan yang nyata antara perlakuan dan kontrol.